Immuno-hyperthermia effected by antibody-conjugated nanoparticles selectively targets and eradicates individual cancer cells. Issue 13 (3rd July 2021) - Kagawa, Tetsuya; Matsumi, Yuki; Aono, Hiromichi; Ohara, Toshiaki; Tazawa, Hiroshi; Shigeyasu, Kunitoshi; Yano, Shuya; Takeda, Sho; Komatsu, Yasuhiro; Hoffman, Robert M.; Fujiwara, Toshiyoshi; Kishimoto, Hiroyuki
ABSTRACT: Hyperthermia has been used for cancer therapy for a long period of time, but has shown limited clinical efficacy. Induction-heating hyperthermia using the combination of magnetic nanoparticles (MNPs) and an alternating magnetic field (AMF), termed magnetic hyperthermia (MHT), has previously shown efficacy in an orthotopic mouse model of disseminated gastric cancer. In the present study, superparamagnetic iron oxide nanoparticles (SPIONs), a type of MNP, were conjugated with an anti-HER2 antibody, trastuzumab and termed anti-HER2-antibody-linked SPION nanoparticles (anti-HER2 SPIONs). Anti-HER2 SPIONs selectively targeted HER2-expressing cancer cells co-cultured along with normal fibroblasts and HER2-negative cancer cells and caused apoptosis only in the HER2-expressing individual cancer cells. The results of the present study show proof-of-concept of a novel hyperthermia technology, immuno-MHT for selective cancer therapy, that targets individual cancer cells. Abbreviations: AMF: alternating magnetic field; DDW: double distilled water; DMEM: Dulbecco's Modified Eagle's; Medium; f: frequency; FBS: fetal bovine serum; FITC: Fluorescein isothiocyanate; GFP: green fluorescent protein; H: amplitude; Hsp: heat shock protein; MHT: magnetic hyperthermia; MNPs: magnetic nanoparticles; PI: propidium iodide; RFP: red fluorescent protein; SPION: superparamagnetic iron oxide (Fe3 O4 ) nanoparticle.